Anomalous excitation facilitation in inhomogeneously broadened Rydberg gases - Letscher, F.; Thomas, O.; Niederpruem, T.; Ott, Herwig; Fleischhauer, Michael (Physical Review A, 2017)
When atomic gases are laser driven to Rydberg states in an off-resonant way, a single Rydberg atom may enhance the excitation rate of surrounding atoms. This leads to a facilitated excitation referred to as Rydberg antiblockade. In the usual facilitation scenario, the detuning of the laser from resonance compensates the interaction shift. Here, we discuss a different excitation mechanism, which we call anomalous facilitation. This occurs on the "wrong side" of the resonance and originates from inhomogeneous broadening. The anomalous facilitation may be seen in experiments of attractively interacting atoms on the blue detuned side, where facilitation is not expected to appear.
CRIS-Team Scopus Importer:2023-03-27